Presentation and Management of Pediatric Orbital Cellulitis. Issue 3 (2011) - Fanella, Sergio; Singer, Alex; Embree, Joanne
Abstract : BACKGROUND: Orbital cellulitis is a serious, vision-threatening infection. OBJECTIVE: To review the epidemiology and clinical data of pediatric orbital cellulitis in Manitoba. METHODS: A 12-year retrospective review was conducted of all children (younger than 18 years of age) with orbital cellulitis admitted to Manitoba's only tertiary pediatric centre. Admission rates for orbital cellulitis were compared over three distinct time periods, based on licensure and funding levels of the heptavalent pneumococcal conjugate vaccine (PCV7) in Manitoba. RESULTS: Thirty-eight patients with orbital cellulitis were identified. Of these, 11% were of Aboriginal ethnicity in contrast with 30% to 40% of children who were admitted for other respiratory illnesses. Subperiosteal abscesses occurred in 31.5%. Only eight patients (21%) required surgery. Follow-up imaging after presentation usually did not indicate a need for subsequent surgical drainage. The mean number of orbital cellulitis cases per 1000 admissions for the following periods – before PCV7 licensure, after licensure and before full provincial funding, and after licensure and full funding – were 0.39, 0.53 and 0.90, respectively. No significant difference was noted among any of the periods as PCV7 coverage increased. CONCLUSIONS: The rate of subperiosteal abscesses was lower than other reports. This may be due to the median age at presentation. In contrast to admissions for most other respiratory infections at the Winnipeg Children's Hospital (Winnipeg, Manitoba), Aboriginal ethnicity was uncommon. Surprisingly, rates of admissions for orbital cellulitis appeared to show an increasing trend with increasing access to PCV7 in Manitoba, although overall the number of cases was very small. Studies into the changing microbiology of orbital cellulitis and sinusitis are warranted.